Penerapan Contextual Teaching and Learning (CTL) dalam Membentuk Karakter Peserta Didik pada Pembelajaran PAI - Kelvi Anggraini; Lannita Sir; Gusmaneli . (GLOBAL SCIENTS PUBLISHER, 2026)
The application of Contextual Teaching and Learning (CTL) in Islamic Religious Education (IRE) holds great potential for effectively shaping pupils’ character. CTL emphasises the connection between the subject matter and the context of students’ real lives, so that moral values are not merely understood cognitively, but are also internalised and manifested in everyday behaviour. This approach encourages students to actively ask questions, discuss, observe their environment, undertake experience-based tasks, and reflect on PAI values in real life. Research and literature reviews from the past 10 years, including a study by Gusmaneli (UIN Imam Bonjol Padang) on the integration of Islamic values into PAI lesson design through a contextual approach, indicate that CTL is capable of enhancing understanding of moral values, student engagement, and positive behavioural changes in the context of honesty, tolerance, and responsibility. Thus, CTL can serve as a relevant character-based learning strategy to be developed in PAI teaching across various levels of education.